-9x= -6x-12
Alguem me ajuda a resolver isso
Soluções para a tarefa
Respondido por
0
Resposta:
x = 4
Explicação passo-a-passo:
-9x = -6x -12
-9x + 12 = -6x
12 = -6x + 9x
12 = 3x
12/3 = x
4 = x
x = 4
se colocar o 4 no lugar do x os dois lados serão iguais
-9x = -6x-12
-9 . 4 = -6 .4 - 12
-36 = -24 - 12
-36 = -36
Perguntas interessantes
Matemática,
8 meses atrás
ENEM,
8 meses atrás
ENEM,
8 meses atrás
Geografia,
10 meses atrás
Matemática,
10 meses atrás
Pedagogia,
1 ano atrás
História,
1 ano atrás
História,
1 ano atrás